2008
DOI: 10.1024/0300-9831.78.45.223
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic Acid-Rich Flaxseed Oil Ingestion Increases Plasma Adiponectin Level in Rats

Abstract: Adiponectin, an adipose-specific secretory protein, exhibits antidiabetic and antiatherogenic properties. The effect of alpha-linolenic acid (ALA) on adiponectin has not been revealed. ALA is included abundantly in vegetable oils such as flaxseed oil. In this study, we attempted to clarify the effect of ALA-rich flaxseed oil (FSO) intake on the adiponectin level in rats. Seven-week-old male Sprague-Dawley rats were fed test diets containing high oleic safflower oil (HOSO) or FSO for 4 weeks. After the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…Experimental data have demonstrated that serum adiponectin correlated directly with oleic acid (MUFA in almonds) and LA (major PUFA in walnuts) in the adipocyte membrane (Perez de Heredia et al, 2009), as well as ALA (Sekine et al, 2008). Although adiponectin correlates with insulin sensitivity (Stefan and Stumvoll, 2002;Spranger et al, 2004), insulin sensitivity did not increase in our study.…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Alcontrasting
confidence: 50%
“…Experimental data have demonstrated that serum adiponectin correlated directly with oleic acid (MUFA in almonds) and LA (major PUFA in walnuts) in the adipocyte membrane (Perez de Heredia et al, 2009), as well as ALA (Sekine et al, 2008). Although adiponectin correlates with insulin sensitivity (Stefan and Stumvoll, 2002;Spranger et al, 2004), insulin sensitivity did not increase in our study.…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Alcontrasting
confidence: 50%
“…In contrast, most studies have shown a reduction in the plasma concentration of adiponectin in obesity (see, e.g., [43]) with very few exceptions [44]. The possibility deserves to be considered that some fat components of the diet employed could be stimulus for adiponectin secretion in view that several nutraceutical products such as fish oil [45], safflower oil [46] or linoleic acid [47] increased adiponectin production in either animals or humans.…”
Section: Discussionmentioning
confidence: 80%
“…This seed, when used as a dietary supplement, has been shown to be beneficial in some pathological processes, as described in previous experimental studies (Hansen, 2006;Nies, Cymbala, Kasten, Lamprecht, & Olson, 2006;Paschos, Magkos, Panagiotakos, Votteas, & Zampelas, 2007;Sekine, Sasanuki, Murano, Aoyama, & Takeuchi, 2008). Flaxseed is a rich source of polyunsaturated fatty acids (PUFAS) and contains an average of 41% oil.…”
Section: Introductionmentioning
confidence: 89%